HUBUNGAN KELEKATAN ORANG TUA DENGAN PRESTASI BELAJAR SISWA TK SANDHY PUTRA TELKOM SUMBAWA - Nilawan; Ayuning Atmasari; Roni Hartono (JURNAL PSIMAWA, 2019)
This study aims to determine the relationship of parental attachment to the learning achievement of TK Sandhy Putra Telkom Sumbawa students. This study uses a quantitative descriptive approach with a type of correlational research to find out or test the relationship between two or more variables. The sampling method in this study used a saturated sampling technique, with a total sample of 81 people. The instrument in this study consisted of a scale of stickiness and learning achievement obtained from reports on the progress of TK Sandhy Putra Telkom Sumbawa students. The instrument validity test refers to the item correlation total score which states that the item is said to be valid if it has an item correlation total score 3 0.3. Instrument reliability test using Alpha Cronbach formula with ? coefficient value 0.868 on the scale of attachment. The results of this study indicate a correlation coefficient of -0.763 with the resulting level of significance of 0.000 (LOS <0.01) means that there is a significant relationship between the level of anxiety with the quality of life of the elderly in Unit I Unit I Sumbawa District Health Center. There is a significant relationship between parent attachment and TK Sandhy Putra Telkom Sumbawa student learning achievement. Negative results (-) show the opposite direction, meaning that the higher the level of attachment of parents, the lower the learning achievement, on the contrary the lower the level of attachment of parents, the higher the learning achievement.